STUDY OF COMPOSITION OF PLANT EXTRACTS, POSSESSING ANTIMICROBIAL EFFECT AGAINST VIBRIO CHOLERAE EL TOR, USING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - O. V. Markina (Журнал микробиологии, эпидемиологии и иммунобиологии, 2016)
Aim. Study the composition of plant extracts using high-performance liquid chromatography (HPLC) and evaluation of their antimicrobial effect against Vibrio cholerae El Tor. Materials and methods. Qualitative and quantitative composition of plant extracts was studied using HPLC. Determination of sensitivity of microorganisms to plant extracts was carried out by diffusion into agar method and serial dilutions method. Results. Antibacterial effect of water, water-alcohol and acetone extracts of roots of Limonium gmelinii L., Berberis vulgaris L. and Glycyrrhiza glabra L. was studied. The most effective methods of extraction of biologically active substances, possessing antimicrobial effect against various strains of V.cholerae El Tor, were determined. Conclusion. The use of HPLC allowed to establish the presence of catechines, alkaloids protoberberines and glycyrrhizic acid in extracts, possessing antimicrobial effect against V.cholerae El Tor strains.